Gender, Religion, and Political Agency: Mapping the Field - Giorgi,Alberta (2016)
This paper provides an introductory review of the literature mapping the gendered analyses of the categories of secularism and secularization from a sociological point of view, with the aim of providing some coordinates and bibliographical references and showing the theoretical and analytical implications of the gendered analyses of secularism in relation to the grammars of contemporary democracy. Firstly, it explores how a gendered analysis contributes to redefining the analytical concepts of secularism and secularization. Secondly, it highlights the contributions of women's, gender, and queer studies to the analysis of secularism and religion. Thirdly, it focuses on the tensions between women's and religious agency, showing how and to what extent the debate internal to the sociology of religion is in fact highly relevant to current sociological analyses.